Introduction - Nataša Vampelj Suhadolnik; Helena Motoh (Asian Studies)
Recent decades have brought the topic of researching East Asian collections in Europe and the world to the forefront of research and academia. The colonial and postcolonial frameworks of collecting practices, the cultural and socio-political settings in which the collectors assembled their collections, as well as the history of displaying East Asian objects in museums and other institutions, were researched both in the political centres of those practices and on their peripheries. In a differently structured approach, the collections of objects themselves came into the focus of the research, including their materiality and their “biographies”, providing a novel perspective on the historiography of collections.